Rust web development : with Warp, Tokio, and Reqwest - Gruber, Bastian (Manning Publications Co., 2023)
Create bulletproof, high-performance web apps and servers with Rust. In Rust Web Development you will learn: Handling the borrow checker in an asynchronous environment Learning the ingredients of an asynchronous Rust stack Creating web APIs and using JSON in Rust Graceful error handling Testing, tracing, logging, and debugging Deploying Rust applications Efficient database access Rust Web Development is a pragmatic, hands-on guide to creating server-based web applications with Rust. If you've designed web servers using Java, NodeJS, or PHP, you'll instantly fall in love with the performance and development experience Rust delivers. Hit the ground running! Author Bastian Gruber's sage advice makes it easy to start tackling complex problems with Rust. You'll learn how to work efficiently using pure Rust, along with important Rust libraries such as tokio for async runtimes, warp for web servers and APIs, and reqwest to run external HTTP requests. About the Technology If you're sick of cookie-cutter web development tools that are slow, resource hungry, and unstable, Rust is the solution. Rust services deliver rock-solid safety guarantees, an amazing developer experience, and even a compiler that automatically prevents common mistakes! About the Book Rust Web Development, teaches you to build server-side web apps using Rust, along with important Rust libraries like tokio for async runtimes, warp for web servers and APIs, and reqwest to run external HTTP requests. The book is packed full of examples, code samples, and pro tips for setting up your projects and organizing your code. As you go, you'll build a complete Q&A web service and iterate on your code chapter-by-chapter, just like a real development project. What's Inside Handle the borrow checker in an asynchronous environment Build web APIs and handle JSON Compose a tech stack for asynchronous Rust development Handle errors gracefully Test, trace, log, and debug Deploy Rust applications to multiple environments About the Reader This book is for web developers familiar with Java, Node, or Go, and the absolute basics of Rust. About the Author Bastian Gruber is a Protocol Engineer at Centrifuge. He was part of the official Rust Async Working Group, and founded the Rust and Tell Berlin MeetUp group. Quotes I always assumed Rust was strictly for areas where I'd use C/C++. This book changed my mind! By the end, I was coding as quickly as I could in JS/Node, but with all the protection of a compiled and type-safe language. I'm a convert! - JD McCormack, Meta Walk with a master as he guides you down the path of creating fast, rock-solid, modern web applications. I would not have thought Rust was well-suited for this. Now I'm looking forward to it. - Christoph Baker, Accenture Industry X A gem for those picking up Rust and struggling. It fills in the blanks where many tutorials fall short. In the end, you'll have a working restful API that you can extend to do your bidding and a solid understanding of how it works. - Walt Stoneburner, Bogart Associates of Northern Virginia.